2023
DOI: 10.1001/jamaoto.2023.0841
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Otologic Disease Among Patients With Primary Ciliary Dyskinesia

Abstract: ImportanceOtologic disease is common among people with primary ciliary dyskinesia (PCD), yet little is known about its spectrum and severity.ObjectiveTo characterize otologic disease among participants with PCD using data from the Ear-Nose-Throat Prospective International Cohort.Design, Setting, and ParticipantsThis cross-sectional analysis of baseline cohort data from February 2020 through July 2022 included participants from 12 specialized centers in 10 countries. Children and adults with PCD diagnoses; rout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…Panel members agreed that patients with PCD often underestimate their upper airway symptoms, which are non-specific and to which they grown accustomed over time, highlighting the need to also consider simple signs in the definitions. [4, 7, 55, 56] This was also shown in a recent study from the ENT Prospective International Cohort of PCD Patients (EPIC-PCD) that reported a lack of correlation between sinonasal and otologic symptoms with objective measurements. [57, 58]…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Panel members agreed that patients with PCD often underestimate their upper airway symptoms, which are non-specific and to which they grown accustomed over time, highlighting the need to also consider simple signs in the definitions. [4, 7, 55, 56] This was also shown in a recent study from the ENT Prospective International Cohort of PCD Patients (EPIC-PCD) that reported a lack of correlation between sinonasal and otologic symptoms with objective measurements. [57, 58]…”
Section: Discussionsupporting
confidence: 52%
“…[46] From the ears, recurrent episodes of acute otitis media (AOM) often progress to severe bilateral otitis media with effusion (OME) and conductive hearing impairment. [711] Acute infections of the nose, sinuses, and ears in PCD, usually involve already impaired upper airways, with a more complicated pathophysiology and course compared to common acute upper airway infections.…”
Section: Introductionmentioning
confidence: 99%
“…We received ethics approval from each participating centre and ethics committee for human research in accordance with local legislation. We obtained informed consent or assent from either participants or parents or caregivers of participants aged ≤14 years as described previously [ 3 , 15 ]. Our reporting conforms with the Strengthening the Reporting of Observational Studies in Epidemiology statement [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…Participants were diagnosed at participating centres following ERS guidelines [ 22 ] as described in previous publications [ 3 , 15 ]. Ultrastructural defects were categorised based on the international consensus guideline for reporting transmission electron microscopy (TEM) results, which defined class 1 (hallmark, namely outer dynein arm defects, outer and inner dynein arm defects and microtubular disorganisation with inner dynein arm defects) and class 2 defects, such as central complex defects [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…While not specific to PCD, the absence of persistent middle ear effusions reduces the likelihood of PCD [ 14 ]. Symptoms include otalgia and often chronic or recurrent otorrhea [ 62 ]. Frequent otitis media leads to significant antibiotic exposure in childhood [ 61 ], and tympanostomy with pressure equalizing tube insertion is frequently pursued.…”
Section: Clinical Features Of Pcdmentioning
confidence: 99%